HUBUNGAN PENGGUNAAN SMARTPHONE DENGAN KUALITAS TIDUR PADA REMAJA DI PERUMAHAN KUTABUMI TANGERANG - Ulfa, Rahma; Sari, Rina Puspita; Wibisono, H. A. Y. G. (Nusantara Hasana Journal, 2021)
Adolescents often have health problems, namely the formation of unhealthy daily habits, one of which is sleep habits. The number of sleep disorders in adolescents will continue to grow along with changes in lifestyle and various other activities that will worsen the quality of sleep in adolescents. Many factors affect sleep quality, including lifestyle factors (smartphone use). Gadgets are technological tools that are currently developing rapidly. Technological developments require teenagers to use gadgets every day, the high use of gadgets at night will lead to insufficient healthy sleep needs in adolescents so that the quality and time of sleep are reduced. Sleep in adolescents has a different side compared to other ages, so many factors cause sleep disorders in adolescents, including lifestyle changes, namely the use of smartphones. Smartphone use can affect a person's sleep quality. This study aims to determine whether there is a relationship between smartphone addiction and sleep quality in adolescents Objective to determine the relationship between smartphone use and sleep quality in adolescents in Kuta Bumi Tangerang Housing Research Methods: This study was quantitative, using a descriptive research design with a Cross Sectional approach. Sampling using Stratified Random Sampling in Kuta Bumi Tangerang Housing. Research Results statistical results using the Continuity Correction test then obtained a P Value, 0.039 smaller than a = 0.05, meaning the null hypothesis (Ho) was rejected, namely there was a relationship between smartphone use and sleep quality in adolescents. Conclusion there is a relationship between smartphone use and sleep quality in adolescents in Kuta Bumu Housing, Tangerang.